ACT-18 SHOULD THE DOSE OF TEMOZOLOMIDE BE DECREASED FOR PATIENTS WITH HIGH-GRADE GLIOMAS WHO ARE ON HEMODIALYSIS?. (16th December 2019) - Muto, Jun; Matsutani, Tomoo; Matsuda, Ryosuke; Kinoshita, Masashi; Oikawa, Mitsuteru; Johan, Pallud; Adachi, Kazuhide; Hirose, Yuichi; Sasaki, Hikaru
Abstract: BACKGROUND: The pharmacokinetics of temozolomide in patients with severe renal impairments (creatinine clearance less than 36 mL/min/m2) or in hemodialysis patients has not been investigated. Temozolomide and its metabolic products are mainly excreted in urine, as retention of these in the body may result in increased adverse events in hemodialysis patients harboring a high-grade glioma. METHODS: Eight hemodialysis patients with high-grade gliomas from seven institutions were included in the study. Patient characteristics, treatment schedule, clinical course, pathological/molecular findings, and adverse events were evaluated. RESULTS: The histopathological diagnoses were Isocitrate dehydrogenase (IDH) wild-type glioblastoma in four cases, Not other specified (NOS) glioblastoma in two cases and IDH-mutant anaplastic astrocytoma in one case. Five of the seven patients completed radiotherapy (48–60 Gy) with concomitant temozolomide (75 mg/m2) followed by adjuvant 5-day temozolomide (150 mg/m2) every 28 days. During the entire course of treatment with temozolomide, severe (Common Terminology Criteria for Adverse Events (CTCAE) more than grade 3) lymphocytopenia occurred in 57%(41.7–61%: non hemodialysis patients data, the same as below), neutropenia in 0%(1–15.4%) and thrombocytopenia in 14%(0–16.7%) of the patients. Generally, the frequency and degree of myelosuppression do not increase in hemodialysis patients with high-grade gliomas. Two of the seven (28.5%) patients died of infectious disease despite having no direct correlation to myelosuppression that is similar rate of 21.9% of the death results from infection in hemodialysis patients in Japan. CONCLUSIONS: The high-grade glioma patients under study on hemodialysis did not require decreasing doses of Temozolomide during concomitant radiochemotherapy and maintenance therapy. However, careful clinical and hematological observation is required to avoid critical hematotoxicity and infection.